Switching Antipsychotics to Support the Physical Health of People With Severe Mental Illness: A Qualitative Study of Patient and Caregiver Perceptions and Experiences - Prachi Kaistha; Megan Beddow; Tom Kingstone; Saeed Farooq; Carolyn Chew-Graham (BJPsych Open)
Aims: People with Severe Mental Illness (SMI) have a reduced life expectancy of 15–20 years compared with the general population. This disparity is largely due to preventable health conditions like cardiovascular disease and diabetes. Certain antipsychotics (APs) can contribute to this increased burden due to their association with cardio-metabolic side-effects. Despite the availability of lower-risk APs, risperidone, olanzapine, and quetiapine remain the most prescribed APs in the UK. Switching to improve cardio-metabolic side-effects is rarely implemented in clinical practice. Improving the physical health of people with SMI is a key NHS priority. We conducted a qualitative study to explore the perceptions and experiences of patients and their caregivers surrounding switching APs for physical health benefits to inform the development of an educational intervention for clinicians to support switching APs.